Panoptes: Servicing Multiple Applications Simultaneously Using Steerable Cameras - Jain, Shubham; Nguyen, Viet; Gruteser, Marco; Bahl, Paramvir (IPSN 2017 : proceedings, 2017 16th ACM/IEEE International Conference on Information Processing in Sensor Networks : 18-20, April 2017, Pittsburgh, Pennsylvania, USA, 2017)
Steerable surveillance cameras offer a unique opportunity to support multiple vision applications simultaneously. However, stateof-art camera systems do not support this as they are often limited to one application per camera. We believe that we should break the one-to-one binding between the steerable camera and the application. By doing this we can quickly move the camera to a new view needed to support a different vision application. When done well, the scheduling algorithm can support a larger number of applications over an existing network of surveillance cameras. With this in mind we developed Panoptes, a technique that virtualizes a camera view and presents a different fixed view to different applications. A scheduler uses camera controls to move the camera appropriately providing the expected view for each application in a timely manner, minimizing the impact on application performance. Experiments with a live camera setup demonstrate that Panoptes can support multiple applications, capturing up to 80% more events of interest in a wide scene, compared to a fixed view camera.